The type specimens of Thysanoptera housed in the Museo de La Plata, Argentina - Salazar Martínez, Ana Ernestina (2017)
Type material of Thysanoptera housed in the collection of the División Entomología, Museo de La Plata, was examined and documented. The collection includes 101 species belonging to two suborders and six families, represented by 39 holotypes, 13 allotypes, 295 paratypes. For each type specimen, reference to the original description, label data, valid name, type category, and locality is given.